Reinventing Apprenticeship and Rites of Passage : An Entry Into the Urban Economy in Sub-Saharan Africa - Easton, Peter (World Bank, Washington, DC, 2012)
The note identifies the essential ingredients - employment, meaning, and self-direction - through examples that represent efforts to fill the void in apprenticeship of adult roles, for impoverished young people thrown out of a traditional framework, and into the vortex of African cities. And seemingly, they succeed best where they manage to "recreate tradition", infusing the customary categories of apprenticeship, and age-group association with new economic direction, and increased self-direction, and definition by the participants. From this brief overview of efforts to assist Africa's impoverished youth in building new identities, the following lessons emerged: An adult education approach works best, insofar as it involves building on the experience, and skills that young people carry, and giving them a determining role in guiding the program. Gainful, and meaningful employment is a cornerstone of new identities, but a vision of the future, be it religious, cultural, or political, and the opportunity to apply it to one's own life, is what forms an enduring perseverance in life. Peer counseling is thus a frequent element of successful programs. Traditional apprenticeship, and youth associations should be utilized as repertoire and resource, based on a continual critique. Discovery of one's environment, and advocacy for change, are critical complements to any effort.